Detection, Attribution, and Future Response of Global Soil Moisture in Summer - Qiao, Liang; Zuo, Zhiyan; Xiao, Dong; Bu, Lulei (Frontiers in Earth Science, 2021)
Soil moisture variations and its relevant feedbacks (e.g. soil moisture-temperature; soil moisture-precipitation) have a crucial impact on the climate system. This study uses reanalysis and Coupled Model Intercomparison Project phase 6 simulations datasets to detect, attribute, and project soil moisture variation. The effect of anthropogenic forcings (greenhouse gases (GHG), anthropogenic aerosols (AA), and land use change (LU)) on soil moisture is much larger in comparison with the natural forcing. The soil moisture shows a drying trend at global scale, which mainly attributed to GHG forcing. The effects of external forcings vary with the regions significantly. Over eastern South America GHG, AA, and natural forcings make soil dry while LU forcing makes the soil wet. Over the severe drying Europe, both all the external forcing including GHG, AA, LU, and natural forcing exhibit drying effect. The optimal fingerprint method detection results show that some of GHG, AA, LU, and natural signals can be detected in soil moisture variations in some regions such as Europe. The soil will keep drying in all scenarios over most parts of globe except Sahel and parts of mid-latitudes Asia. With the increase of anthropogenic emissions, the variation of global soil moisture will be more extreme, especially in hotspots where the land-atmosphere coupling is intensive. The drying trend of soil moisture will be much larger on the surface than middle and deep layers in the future, and this phenomenon will be more severe under the high emission scenario. It may be affected by increased evaporation and the effect of carbon dioxide fertilization caused by global warming.